2021
DOI: 10.1155/2021/8414503
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Intrusion Detection Systems in RPL Routing Protocol Based on Machine Learning for Internet of Things Applications

Abstract: IPv6 routing protocol for low-power and lossy networks (RPL) has been developed as a routing agent in low-power and lossy networks (LLN), where nodes’ resource constraint nature is challenging. This protocol operates at the network layer and can create routing and optimally distribute routing information between nodes. RPL is a low-power, high-throughput IPv6 routing protocol that uses distance vectors. Each sensor-to-wire network router has a collection of fixed parents and a preferred parent on the path to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 168 publications
0
5
0
Order By: Relevance
“…[18] proposed a service provider affordability via energy optimization that could optimize service provider network operational cost to sustainability and affordable services between both customers and service providers. In LLNs, RPL (Routing Protocol for LLNs) [19] is the first routing protocol proposed by IETF, where some aspects still need to be improved. Hwang et al.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…[18] proposed a service provider affordability via energy optimization that could optimize service provider network operational cost to sustainability and affordable services between both customers and service providers. In LLNs, RPL (Routing Protocol for LLNs) [19] is the first routing protocol proposed by IETF, where some aspects still need to be improved. Hwang et al.…”
Section: Related Workmentioning
confidence: 99%
“…In SoDIP6, Dawadi et al [18] proposed a service provider affordability via energy optimization that could optimize service provider network operational cost to sustainability and affordable services between both customers and service providers. In LLNs, RPL (Routing Protocol for LLNs) [19] is the first routing protocol proposed by IETF, where some aspects still need to be improved. Hwang et al [20] proposed a Wireless Shortest Path Heuristic (W-SPH) mechanism to construct a multicast tree, which could build an effective routing topology for multicast traffic and yield higher energy efficiency.…”
Section: Routing Protocols In Ipv6 Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Seyfollahi et al 12 reviewed machine learning techniques used in designing intrusion detection systems for the Low-Power and Lossy Networks (RPL) protocol. The study also identified open issues and challenges related to their study's domain.…”
Section: Related Workmentioning
confidence: 99%
“…However, the resource-limited nature of IoT devices and critical smart infrastructures motivate hackers to launch various attacks within the RPL-IIoT scenario, and RPL security is paramount. A common method of RPL-IIoT attack detection is to employ a machine learning (ML)-based intrusion detection system (IDS) [ 3 , 4 ]. However, most traditional ML-based IDS solutions are centralised and do not have the flexibility to detect the variety and full range of RPL attacks on IIoT applications [ 5 ].…”
Section: Introductionmentioning
confidence: 99%